Neutrophil Emigration in the Skin, Lungs, and Peritoneum: Different Requirements for CD11/CD18 Revealed by CD18-deficient Mice - Mizgerd, Joseph P. (The Rockefeller University Press, 1997)
To determine the role of CD11/CD18 complexes in neutrophil emigration, inflammation was induced in the skin, lungs, or peritoneum of mutant mice deficient in CD18 (CD18(−/−) mutants). Peripheral blood of CD18(−/−) mutants contained 11-fold more neutrophils than did blood of wild-type (WT) mice. During irritant dermatitis induced by topical application of croton oil, the number of emigrated neutrophils in histological sections of dermis was 98% less in CD18(−/−) mutants than in WT mice. During Streptococcus pneumoniae pneumonia, neutrophil emigration in CD18(−/−) mutants was not reduced. These data are consistent with expectations based on studies using blocking antibodies to inhibit CD11/CD18 complexes, and on observations of humans lacking CD11/CD18 complexes. The number of emigrated neutrophils in lung sections during Escherichia coli pneumonia, or in peritoneal lavage fluid after 4 h of S. pneumoniae peritonitis, was not reduced in CD18(−/−) mutants, but rather was greater than the WT values (240 ± 30 and 220 ± 30% WT, respectively). Also, there was no inhibition of neutrophil emigration during sterile peritonitis induced by intraperitoneal injection of thioglycollate (90 ± 20% WT). These data contrast with expectations. Whereas CD11/CD18 complexes are essential to the dermal emigration of neutrophils during acute dermatitis, CD18(−/−) mutant mice demonstrate surprising alternative pathways for neutrophil emigration during pneumonia or peritonitis.